The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1021/acsenergylett.9b01423
|View full text |Cite
|
Sign up to set email alerts
|

V2+/V3+ Redox Kinetics on Glassy Carbon in Acidic Electrolytes for Vanadium Redox Flow Batteries

Abstract: Vanadium redox flow batteries are a promising technology for energy storage, yet the mechanism of the kinetically limiting V 2+ /V 3+ redox reaction remains poorly understood. Here, we elucidate the impact of anion complexation on V 2+ /V 3+ kinetics on a glassy carbon electrode in three common electrolytes: hydrochloric acid, sulfuric acid, and mixed HCl/H 2 SO 4 . The V 2+ /V 3+ kinetics are ∼2.5 times faster in HCl and have lower apparent activation energies than those in H 2 SO 4 or HCl/H 2 SO 4 . We also … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
57
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(60 citation statements)
references
References 53 publications
2
57
0
Order By: Relevance
“…[3] Currently,a sthe representative of aqueous RFBs using redox species dissolved in aqueous solutions,vanadium-based RFBs have been successfully commercialized. [4] In this context, aqueous RFBs have shown clear advantages compared with nonaqueous candidates,s uch as low cost, noninflammability,high power, and many available ion-selective membranes. [5] However,i nc onventional aqueous RFBs,t he choice of redox species is limited to metal-based active materials,s uch as vanadium-based ions.T he relatively high cost of transition metals and limited energy density have impeded their extensive application.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[3] Currently,a sthe representative of aqueous RFBs using redox species dissolved in aqueous solutions,vanadium-based RFBs have been successfully commercialized. [4] In this context, aqueous RFBs have shown clear advantages compared with nonaqueous candidates,s uch as low cost, noninflammability,high power, and many available ion-selective membranes. [5] However,i nc onventional aqueous RFBs,t he choice of redox species is limited to metal-based active materials,s uch as vanadium-based ions.T he relatively high cost of transition metals and limited energy density have impeded their extensive application.…”
Section: Introductionmentioning
confidence: 99%
“…[5] However,i nc onventional aqueous RFBs,t he choice of redox species is limited to metal-based active materials,s uch as vanadium-based ions.T he relatively high cost of transition metals and limited energy density have impeded their extensive application. [4,6] Tr emendous research efforts have been made on exploring next-generation flow battery technologies as potential alternatives,s uch as zincbased flow batteries or aqueous organic RFBs. [7] Zinc-based flow batteries have high working voltage,b ut they are commonly suffering ashort cycle life because of zinc dendrite issues,e specially under high current density.…”
Section: Introductionmentioning
confidence: 99%
“…[ 12 ] Agarwal et al. [ 16 ] investigated the reaction mechanism of the V 2+ /V 3+ reaction in HCl, HCl/H 2 SO 4 , and H 2 SO 4 electrolytes, and found that a bridging ligand was formed during the reaction. They suggested that higher polarizability of the *Cl bridge in HCl than the *OH bridge in conventional H 2 SO 4 or HCl/H 2 SO 4 rendered an enhanced electron transfer rate.…”
Section: Aqueous Inorganic Redox Flow Batteries (Airfbs)mentioning
confidence: 99%
“…Counter anions (such as Cl − ) can exchange with the H 2 O ligand in the primary solvation shell, which has been found to play a vital role in tuning the thermal and chemical stability of hydrated vanadium cations and their reaction pathways. [12] Agarwal et al [16] investigated the reaction mechanism of the V 2+ /V 3+ reaction in HCl, HCl/H 2 SO 4 , and H 2 SO 4 electrolytes, and found that a bridging ligand was formed during the reaction. They suggested that higher polarizability of the *Cl bridge in HCl than the *OH bridge in conventional H 2 SO 4 or HCl/H 2 SO 4 rendered an enhanced electron transfer rate.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, as the representative of aqueous RFBs using redox species dissolved in aqueous solutions, vanadium‐based RFBs have been successfully commercialized [4] . In this context, aqueous RFBs have shown clear advantages compared with nonaqueous candidates, such as low cost, noninflammability, high power, and many available ion‐selective membranes [5] .…”
Section: Introductionmentioning
confidence: 99%